Institutional Constraints as an Obstacle for Prioritizing Nursing Interventions During the COVID-19 Pandemic-Critical Care Nurses' Experiences - Åsa Engström PhD, RN; Angelica Fredholm PhD, RN; Anna Nordin PhD, RN; Maria Andersson PhD, RN (SAGE Publishing, 2022)
Introduction The demands of the pandemic such as staff shortages and limited resources combined with new guidelines regarding infection control may have required the prioritizing of nursing interventions. Objectives The aim of this study was to describe critical care nurses' experiences of prioritizing nursing interventions for patients with COVID-19 in intensive care units (ICUs) during the pandemic. Method A qualitative descriptive study was gathered from open-ended questions included in a cross-sectional online questionnaire. Characteristics were presented using descriptive statistics, and open-ended questions were analyzed using qualitative content analysis with an inductive approach. The study was conducted in Sweden and focused on critical care nurses working in ICUs during spring 2021 and the second year of the COVID-19 pandemic. Results During the COVID-19 pandemic, 87% of the critical care nurses had provided orientations for new co-workers, and 52% had supervised intensive care nursing students. In all, 70 answered the question of whether they had prioritized nursing care differently during the pandemic; 86% reported that they had and 14% had not. The qualitative analysis resulted in one theme, Institutional constraints as an obstacle for nursing interventions, with three categories: Prioritizing lifesaving interventions, Performing nursing interventions less frequently, and Not able to provide the nursing care I wish to provide. Conclusion Institutional constraints as an obstacle for nursing interventions is the overall theme. It illustrates how critical care nurses have been forced to prioritize, thereby not being able to provide the nursing interventions they wanted to do provide, and it describes their feelings in this situation. The nurses need recovery and possibilities for reflection. The organization must also recover and not only return to how it was before the pandemic but also to learn from recent events and take actions to reduce the long-term effects on staffing.